3D B-spline curve construction from orthogonal views with self-overlapping projection segments. (February 2016) - Lu, Yang; Yong, Jun-Hai; Shi, Kan-Le; Song, Hai-Chuan; Ye, Tian-Yu
Abstract: Constructing B-spline curves from orthogonal views is a common operation in the process of car modelling. Existing reconstructing methods for 3D free-form curves cannot effectively handle the situation where the projection curves in the input views are self-overlapping, which appears frequently in practice. In this paper we focus on solving the problem above. We track the input views simultaneously and generate an ordered set of sampling space points. Then we reorganize the planar points in each view according to the sampling points. Weight values are assigned to all points, and the points around the overlapping segments are split into multiple ones. Then the resulting curve can be evaluated through minimizing the constructed energy function. Examples show the efficiency of our method. Abstract : Graphical abstract: Abstract : Highlights: We propose a stepwise tracking method to generate ordered 3D points from two input orthogonal views. We propose a method to construct 3D B-spline curves from planar views through minimizing the energy function with weight values. The method can efficiently detect the situation of self-overlapping for curve segments from input views.